Кримінально-правова характеристика бюджетних коштів як предмета кримінальних правопорушень - Топчій, Василь Васильович; Мамка, Григорій Миколайович (УДФСУ, 2020)
У цій статті зазначається, що предметом злочинного посягання у кримінальних провадженнях щодо нецільового використання бюджетних коштів є витрати бюджету у великих та особливо великих розмірах, що здебільшого представлені у формі видатків і витрачаються на цілі, які не відповідають бюджетним призначенням, установленим Законом «Про Державний бюджет України» або рішенням про місцевий бюджет, напрямам використання бюджетних коштів, визначеним у паспорті бюджетної програми у разі застосування програмно-цільового методу в бюджетному процесі або в порядку використання бюджетних коштів, бюджетним асигнуванням розпису бюджету, кошторису, плану використання бюджетних коштів. Вказується, що таке розуміння предмета злочинного посягання має вагоме значення для розслідування вказаної категорії протиправних діянь, оскільки уточнює, у якій формі він відображений та з якого моменту можуть учинятися бюджетні посягання у формі нецільового використання бюджетних коштів.

In this article marked, that the article of criminal trespass in criminal realizations in relation to the no-purpose use of budgetary facilities are charges of budget in large and especially large sizes, that is mostly presented in form charges and spent on aims, that does not answer the budgetary setting, set Law on the State budget of Ukraine or decision about a local budget, to directions of the use of budgetary facility, certain in passport budgetary program in case of application programmatic-having a special purpose method in budgetary process or in order of the use budgetary facility, budgetary assignation painting budget, estimate, plan the use budgetary facility. Specified, that such understanding of the article of criminal trespass has a ponderable value for investigation of the indicated category of illegal acts, as specifies, in what form he is represented and out of what moment budgetary encroachments can be made in form the no-purpose use of budgetary facilities. Grounded, that the article of criminal trespass in criminal realizations in relation to the no-purpose use of budgetary facilities are charges of budget in large and especially large sizes, that is mostly presented in form charges and spent on aims that does not answer the budgetary setting, by the set Law on the State budget of Ukraine (by a decision about a local budget), to directions of the use of budgetary facilities, certain in the passport of the budgetary program (in case of application of programmatic-having a special purpose method in a budgetary process) or in order of the use of budgetary facility, budgetary assignation (to painting of budget, estimate, plan of the use of budgetary facilities). Such understanding of the article of criminal trespass has a ponderable value for investigation of the indicated category of протиправних acts, as specifies, in what form he is represented and out of what moment budgetary encroachments can be made in form the no-purpose use of budgetary facilities
Keywords: злочин; злочинність; предмет злочину; нецільове використання бюджетних коштів; crime; criminality; article of crime; no-purpose use of budgetary facilities